2015
DOI: 10.3174/ajnr.a4346
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Resting-State Network on Lateralization of Functional Connectivity in Mesial Temporal Lobe Epilepsy

Abstract: BACKGROUND AND PURPOSE:Although most studies on epilepsy have focused on the epileptogenic zone, epilepsy is a system-level disease characterized by aberrant neuronal synchronization among groups of neurons. Increasingly, studies have indicated that mesial temporal lobe epilepsy may be a network-level disease; however, few investigations have examined resting-state functional connectivity of the entire brain, particularly in patients with mesial temporal lobe epilepsy and hippocampal sclerosis. This study prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
2
19
1
Order By: Relevance
“…However, these modulating factors are not always methodologically controlled for in the studies that can have relatively large but heterogeneous samples. In a machine learning study, Su, An, Ma, Qiu, and Hu () investigated FC at rest in right TLE patients and matched healthy subjects to identify connections that distinguish the patients from the controls. Interestingly, their results showed reduced FC within the right hemisphere along with FC strengthening within the preserved left hemisphere, which was interpreted as a compensatory mechanism (Su et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these modulating factors are not always methodologically controlled for in the studies that can have relatively large but heterogeneous samples. In a machine learning study, Su, An, Ma, Qiu, and Hu () investigated FC at rest in right TLE patients and matched healthy subjects to identify connections that distinguish the patients from the controls. Interestingly, their results showed reduced FC within the right hemisphere along with FC strengthening within the preserved left hemisphere, which was interpreted as a compensatory mechanism (Su et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a machine learning study, Su, An, Ma, Qiu, and Hu () investigated FC at rest in right TLE patients and matched healthy subjects to identify connections that distinguish the patients from the controls. Interestingly, their results showed reduced FC within the right hemisphere along with FC strengthening within the preserved left hemisphere, which was interpreted as a compensatory mechanism (Su et al, ). Current methods allow for the identification and description of networks in a remarkable complexity, there remains scope for a clearer explanatory understanding of how and importantly what these networks compute (Mill et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have established that TLE affects a distributed neural network, with widespread extratemporal effects, rather than having a single focal epileptogenic source [23][24][25][26]. Based on both structural and functional connectivity (FC) analyses, accumulating evidence suggests that brain-networks in TLE patients are pathologically altered [27][28][29][30]. Hsiao et al [31] investigated FC alterations in the default mode network (DMN) in TLE, using resting-state spike-free MEG recordings.…”
Section: Introductionmentioning
confidence: 99%
“…This inherent network laterality can be altered by influence of various genetic and environmental factors, and this change reflects interhemispheric variation in perception processing. In several previous studies, this alteration was associated with the deterioration of auditory and psychologic symptoms in various neuropsychiatric conditions, such as epilepsy, cognitive impairment, and mild traumatic brain injury (3,4). Furthermore, some studies have reported that cognitive training effects the lateralization of intrinsic networks in healthy older adults and stroke patients (5,6).…”
Section: Introductionmentioning
confidence: 90%
“…In addition, sagittal structural three-dimensional (3D) T1-weighted images (T1WI) were acquired to create templates for anatomical brain image registration. Acquisition parameters were as follows: TR = 8.1 ms, TE = 3.7 ms, flip angle = 8°, FOV = 236 × 236 mm 2 , and voxel size = 1 × 1 × 1 mm 3 . Furthermore, T2-weighted axial images were acquired to screen for gross structural abnormalities in the temporal bones or brain.…”
Section: Acquisition Of Mrimentioning
confidence: 99%